PDF Photodynamic effect of Rose Bengal activated by low-level laser light on S. aureus : Qusay K. Abbas*, Layla M. Hassan - الطالب قصي خضير و د ليلى (Iraqi Journal of Laser, 2022)
Abstract: Background: Staphylococcus aureus is Gram-positive bacteria that lives as a normal flora in living organisms but can be pathogenic to humans. Although a relatively unspectacular, nonmotile coccoid bacterium, S. aureus is a dangerous human pathogen in both community-acquired and nosocomial infections. Due to the increasing emergence of new strains of this antibiotic-resistant bacteria, it has become essential to approach different methods to control this pathogen. One of these methods is the antimicrobial photodynamic inactivation process using a low-level laser, in this paper, the Photodynamic effects of Rose Bengal and LLLL on the virulence factors of S.aureus were evaluated. The aim of the study The present study aims to evaluate the Photodynamic effects on S. aureus using laser irradiation and Rose Bengal as an external photosensitizer. Methods: sixty samples from sputum were taken. Then ten isolated from these samples were chosen to be under the study, where RB was used at a concentatin of 100 μg/ml that is activated by diode laser (532 nm) with power density of 1 W/m2and exposure time (1, 2& 3) minute. Results: show that there is no effect on the inhibition of virulence factors except at the last minute, that is, the virulence factors decrease at the third minute only in the absence of a photosensitizer agent, while there is a direct effect of activated Rose Bengal on S. aureus isolated from the sputum of Iraqi patients with pneumonia, where all times of exposure of (RB + 532 nm) were effect on the virulence factors by inhibiting it. Conclusions: show that the diode laser of 532 nm has no effect on the virulence factor of S. aureus isolated from sputum except at the third minute, while RB activated by diode laser (532 nm) have an effective action on all virulence factors of S. aureus isolated from sputum at all times of exposure, accordingly, it was concluded that when using a laser diode alone, the bacterial viability decreases at the third minute only, While when using Rose Bengal activated by a diode laser, the viability of bacteria is reduced at all times of exposure.